What is the value of volunteers for non-profit organizations? - Kristmundsson, Ómar H.; Hrafnsdóttir, Steinunn (Veftímaritið Stjórnmál og stjórnsýsla, 2013)
A study on the value of volunteers as resources for non-profit organizations in welfare services in Iceland is described. The topic relates to an international academic discussion on the volunteer function within non-profit organizations. The discussion has until now focused more on the supply of volunteers than demand. This article is to meet the need for analysis of how non-profit organization use volunteers as resources. The study is based on the authors’ database from 2011 on the majority of active non-profit organizations in welfare services in Iceland and an analysis of their respective web sites in 2013. It is concluded that even though volunteers exist within most non-profits, their role cannot be considered essential and is limited to governance boards and time-limited activities, such as fund raising. The level of activity of volunteers depends on the operational size and the role of the organization. Their input decreases with increased number of paid staff and their activity is less within non-profit service providers than member oriented and campaign organizations. The finding is in harmony with international research, for example on the effects of professionalization within the third sector. The research conclusion is noteworthy having in mind international research which indicates that the interest of the general public to become volunteers has essentially not changed in the past decades. The current findings raise the issue of how well traditional organizations of non-profits meet the needs of the public for volunteering. Lýst er niðurstöðum rannsóknar á mikilvægi sjálfboðaliða sem auðlindar fyrir félagasamtök í velferðarþjónustu á Íslandi. Viðfangsefnið snýr að alþjóðlegri fræðilegri umræðu um hlutverk sjálfboðaliða innan félagasamtaka. Sú umræða hefur fram að þessu beinst meira að framboði sjálfboðastarfs fremur en eftirspurn félagasamtaka eftir slíku framlagi. Rannsókninni er ætlað að bæta úr þörf á að greina hvernig félagasamtök nýta sér sjálfboðaliða. Notast er við tvö gagnasöfn höfunda, ...